Enhancing Visitor Satisfaction Through Service Quality: A Study of the Traditional Tourism Village of Lewokluok - Ola, Katarina Jesika Bulu; Risfandini, Andini; Ulya, Ayu Fitriatul (Proceedings of International Conference of Graduate School on Sustainability, 2025)
East Nusa Tenggara, particularly the East Flores Regency, presents a diverse range of tourist attractions, with the Traditional Tourism Village of Lewokluok emerging as a notable destination. Renowned for its authentic village atmosphere, cultural heritage, and unique Koke Bale traditional houses, Lewokluok has gained national recognition and attracted nearly 30,000 visitors from July 2021 to December 2023. Despite its appeal, the village faces challenges in service quality, which is crucial for enhancing visitor satisfaction. This research aims to exploring how service quality dimensions, aligned with sustainable tourism principles, affect visitor satisfaction in settings prioritizing environmental and cultural preservation. This study investigates the relationship between service quality and tourist satisfaction, utilizing a quantitative approach with a survey of 100 tourists. Findings reveal that high service quality significantly influences visitor satisfaction, Key service dimensions, including reliability and responsiveness, play a critical role in shaping the tourist experience. Recommendations for improving service quality and promoting the village's unique cultural offerings are proposed to enhance visitor satisfaction and ensure sustainable tourism development in Lewokluok.